Mixture for electrochemical device, mixture sheet for electrochemical device, electrochemical device, and method for manufacturing mixture sheet for electrochemical device

JP2025036339AActive Publication Date: 2025-03-14DAIKIN INDUSTRIES LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024147606
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-08-29
Publication Date
2025-03-14
Estimated Expiration
2044-08-29

AI Technical Summary

Benefits of technology

【0022】 本開示によれば、シート強度を改善できる電気化学デバイス用合剤、電気化学デバイス用合剤シート、電気化学デバイス、及び、電気化学デバイス用合剤シートの製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036339000001
    Figure 2025036339000001
  • Figure 2025036339000002
    Figure 2025036339000002
  • Figure 2025036339000003
    Figure 2025036339000003
Patent Text Reader

Abstract

To provide a mixture for an electrochemical device which can improve sheet strength, a mixture sheet for an electrochemical device, an electrochemical device, and a method for manufacturing a mixture sheet for an electrochemical device.SOLUTION: A mixture for an electrochemical device contains fluoropolyether, a fibrillable resin, and an electrochemical device material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a mixture for an electrochemical device, a mixture sheet for an electrochemical device, an electrochemical device, and a method for producing a mixture sheet for an electrochemical device. [Background technology]

[0002] 2. Description of the Related Art With the trend toward lighter and smaller electric appliances in recent years, the development of electrochemical devices having high energy density, such as lithium ion secondary batteries, has progressed.

[0003] As technologies relating to electrochemical devices, Patent Document 1 discloses an electrode for a secondary battery using a powdered active material, a conductive material, and a fluorine-containing polymer resin, and Patent Document 2 discloses a self-supporting solid composite electrolyte membrane using solid ion-conductive inorganic particles and a tetrafluoroethylene (co)polymer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-026984 A [Patent Document 2] Special Publication No. 2022-546129 Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide a mixture for electrochemical devices, a mixture sheet for electrochemical devices, an electrochemical device, and a method for producing a mixture sheet for electrochemical devices, which are capable of improving sheet strength. [Means for solving the problem]

[0006] The present disclosure (1) is a mixture for electrochemical devices, comprising a fluoropolyether, a fibrillar resin, and an electrochemical device material.

[0007] The present disclosure (2) relates to the mixture for electrochemical devices according to the present disclosure (1), wherein the fluoropolyether is at least one of the following formulae (1) to (4): (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (4)R 4 -Rb 4 -R 4 (In the formula, Ra 1 ~Ra 3 are each independently a polyoxyalkylene group containing 4 to 50 oxyalkylene units not containing fluorine, Ra 1 ~Ra 3 Each oxyalkylene unit is independently -CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 4 are each independently a fluoropolyether group represented by the following formula (5): R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 4 are each independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent. (5)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0008] This disclosure (3) relates to the Ra 1 ~Ra 3 are each independently a polyoxyalkylene group represented by the following formula (Ra-I): (Ra-I): -(CH 2 CH 2 O)r(CH 2 CH(CH 3 )O)s(CH 2 CH(CH 2 CH 3 )O)t(CH 2 CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

[0009] This disclosure (4) relates to the Ra 1 ~Ra 3 The mixture for electrochemical devices according to the present disclosure (2) or (3), wherein the number average molecular weight of the mixture is 40 to 4,000.

[0010] The present disclosure (5) is the mixture for electrochemical devices according to any one of the present disclosures (2) to (4), in which the Rfs are each independently a fluoropolyether group represented by the following formula (Rf-I): Formula (Rf-I): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 Rc 6 )d-(OC2 F 4 )e-(OCF 2 )f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeat unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e, and f is 1 or greater.

[0011] The present disclosure (6) is the mixture for electrochemical devices according to any one of the present disclosures (2) to (5), in which the Rfs are each independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary.

[0012] This disclosure (7) relates to the R 1 ~R 3are each independently a methyl group, an ethyl group, a trifluoromethyl group, or a pentafluoroethyl group.

[0013] The present disclosure (8) is the mixture for electrochemical devices according to any one of the present disclosures (1) to (7), wherein the fibrillar resin is polytetrafluoroethylene.

[0014] The present disclosure (9) is the mixture for electrochemical devices according to any one of the present disclosures (1) to (8), wherein the electrochemical device material is an electrode active material.

[0015] The present disclosure (10) is the mixture for electrochemical devices according to any one of the present disclosures (1) to (9), wherein the fluoropolyether is liquid at any temperature between 25°C and 80°C.

[0016] The present disclosure (11) is a mixture for electrochemical devices according to any one of the present disclosures (1) to (10), in which the content of the polyalkylene oxide represented by the following formula (6) is less than 20 mass %. (6)R 1B -(OCHR 1A (CH 2 )jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is an integer of 0 or 1 to 2, R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

[0017] The present disclosure (12) is a mixture for electrochemical device according to any one of the present disclosures (1) to (11), which contains a conductive assistant.

[0018] The present disclosure (13) is a mixture sheet for electrochemical devices, including the mixture for electrochemical devices according to any one of the present disclosures (1) to (12).

[0019] The present disclosure (14) is an electrochemical device using the mixture sheet for electrochemical devices according to the present disclosure (13).

[0020] The present disclosure (15) relates to a process (1) for mixing a fluoropolyether, a fibrillar resin, and an electrochemical device material; and (2) rolling the mixture for use in electrochemical devices obtained in the step (1) into a sheet.

[0021] The present disclosure (16) is the manufacturing method according to the present disclosure (15), wherein the fibrillar resin is polytetrafluoroethylene. Effect of the Invention

[0022] Advantageous Effects of Invention According to the present disclosure, it is possible to provide a mixture for electrochemical devices, a mixture sheet for electrochemical devices, an electrochemical device, and a method for manufacturing a mixture sheet for electrochemical devices, which are capable of improving sheet strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present disclosure will now be described in detail.

[0024] <Compounds for electrochemical devices> The present disclosure relates to a mixture for an electrochemical device, comprising a fluoropolyether, a fibrillar resin, and an electrochemical device material.

[0025] The mixture for electrochemical devices according to the present disclosure has the above-mentioned configuration, and therefore can improve the strength of electrode sheets and solid electrolyte sheets. This is believed to be because the kneading of the fluoropolyether and the fibrillar resin improves the cohesion between the powders, promoting the generation of fibrils. In addition, by promoting the generation of fibrils, it is possible to reduce the amount of binder used and improve the energy density of electrochemical devices.

[0026] As the fluoropolyether, at least one of the following formulae (1) to (4) can be suitably used. These compounds can enhance the effect of improving sheet strength, and further improve the initial discharge capacity and the amount of gas generation. This is because Rb 1 ~Rb 4 This is believed to be because the portion of Ra exerts good lubricity and improves the packing density. 1 ~Ra 3 The portion may provide ion conductivity. (1)R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2)R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3)R 3 -Rb 3 -O-Ra 3 -R 3 (4)R 4 -Rb 4 -R 4 (In the formula, Ra 1 ~Ra 3 are each independently a polyoxyalkylene group containing 4 to 50 oxyalkylene units not containing fluorine, Ra 1 ~Ra 3 Each oxyalkylene unit is independently -CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 4are each independently a fluoropolyether group represented by the following formula (5): R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 4 are each independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent. (5)-Rf 1 -Rf-O-Rf 2 - (In the formula, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

[0027] Ra 1 ~Ra 3 The oxyalkylene unit is -CH 2 In the case of CH(J)O-, the alkyl group of J may be linear or branched, but is preferably linear. The alkyl group of J preferably has 1 to 3 carbon atoms. Examples of the aryl group represented by J include a phenyl group, a 4-nitrophenyl group, a 4-acetylaminophenyl group, and a 4-methanesulfonylphenyl group.

[0028] Ra 1 ~Ra 3 are preferably each independently a polyoxyalkylene group represented by the following formula (Ra-I). (Ra-I): -(CH 2 CH 2 O)r-(CH 2 CH(CH 3 )O)s-(CH 2 CH(CH 2 CH 3)O)t-(CH 2 CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

[0029] In the above formula (Ra-I), r is preferably 1 or more, more preferably 2 or more, and is preferably 30 or less, more preferably 20 or less. s, t and u are preferably 10 or less, more preferably 5 or less, and further preferably 0. r+s+t+u is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.

[0030] Ra 1 ~Ra 3 The number average molecular weight of is preferably 40 or more, more preferably 100 or more, and is preferably 4000 or less, more preferably 1000 or less. In the present specification, Ra 1 ~Ra 3 The number average molecular weight of 1 This is a value measured by H-NMR.

[0031] Rb 1 ~Rb 4 In the above formula (5), Rf 1 and Rf 2 The alkylene group may be linear or branched, but is preferably linear. Rf 1 and Rf 2 The alkylene group is preferably a fluorine-substituted alkylene group substituted with a fluorine atom. Rf 1 and Rf 2 The alkylene group preferably has 1 to 3 carbon atoms.

[0032] Rb 1 ~Rb 4 In the above formula (5), Rf may have a ring structure.

[0033] Rb 1 ~Rb 4 In the above formula (5), Rf is preferably a fluoropolyether group represented by the following formula (Rf-I). Formula (Rf-I): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 Rc 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer of 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeat unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e, and f is 1 or greater.

[0034] Rc is preferably a hydrogen atom or a fluorine atom, and more preferably a fluorine atom, That is, Rf in the formula (5) is preferably a perfluoropolyether group.

[0035] It is preferable that a, b, c, d, e and f each independently represent an integer of 0 to 100.

[0036] The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, and may be 15 or more or 20 or more. The sum of a, b, c, d, e and f is preferably 100 or less, more preferably 60 or less, and may be 50 or less or 30 or less.

[0037] Each repeat unit denoted by a, b, c, d, e, or f may be linear or branched. -(OC 6 F 12 )- is, for example, -(OCF 2 CF 2 CF 2 CF 2 CF 2 CF 2 )-, -(OCF(CF 3 )CF 2 CF 2 CF 2 CF 2 )-, -(OCF 2 CF(CF 3 )CF 2 CF 2 CF 2 )-, -(OCF 2 CF 2 CF(CF 3 )CF 2 CF 2 )-, -(OCF 2 CF 2 CF 2 CF(CF 3 )CF 2 )-, -(OCF 2 CF 2 CF 2 CF 2 CF(CF 3 ))-. -(OC 5 F 10 )- is, for example, -(OCF 2 CF 2 CF 2 CF 2 CF 2 )-, -(OCF(CF 3 )CF 2 CF 2 CF 2 )-, -(OCF 2 CF(CF 3 )CF 2 CF 2 )-, -(OCF 2 CF 2 CF(CF 3 )CF 2 )-, -(OCF 2 CF2 CF 2 CF(CF 3 ))-. -(OC 4 F 8 )- is, for example, -(OCF 2 CF 2 CF 2 CF 2 )-, -(OCF(CF 3 )CF 2 CF 2 )-, -(OCF 2 CF(CF 3 )CF 2 )-, -(OCF 2 CF 2 CF(CF 3 ))-, -(OC(CF 3 ) 2 CF 2 )-, -(OCF 2 C(CF 3 ) 2 )-, -(OCF(CF 3 )CF(CF 3 ))-, -(OCF(C 2 F 5 )CF 2 )-, -(OCF 2 CF(C 2 F 5 ))-. -(OC 3 F 6 )-(i.e., in the above formula (Rf-I), all Rc are fluorine atoms) is, for example, -(OCF 2 CF 2 CF 2 )-, -(OCF(CF 3 )CF 2 )-, -(OCF 2 CF(CF 3 ))-. -(OC 2 F 4 )- is, for example, -(OCF 2 CF 2 )-, -(OCF(CF 3 ))-.

[0038] Rf may be a group represented by any one of the following formulas (Rf-II) to (Rf-IV). Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer of 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer of 1 to 200; The sum of c, d, e, and f is 2 or more, The order of the repeating units marked with c, d, e, or f is arbitrary. Formula (Rf-I-III): -(R 20 -R 21 )g- (In the formula, R 20 is OCF 2 Or O.C. 2 F 4 and R 21 is O.C. 2 F 4 , O.C. 3 F 6 , O.C. 4 F 8 , O.C. 5 F 10 and O.C. 6 F 12 or a combination of two or three groups selected from these groups, g is an integer from 2 to 100. Formula (Rf-I-IV): -(OC 6 F 12 )a-(OC 5F 10 )b-(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, e is an integer of 1 to 200, a, b, c, d, and f each independently represent an integer of 0 to 200; The order of each repeating unit with a, b, c, d, e, or f is arbitrary. Formula (Rf-IV): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, f is an integer of 1 to 200, a, b, c, d, and e each independently represent an integer of 0 to 200; The order of each repeating unit with a, b, c, d, e, or f is arbitrary.

[0039] In the above formula (Rf-II), d is preferably 5 to 200, more preferably 10 to 100, and further preferably 15 to 50, and may be 25 to 35. The above formula (Rf-II) is preferably -(OCF 2 CF 2 CF 2 )d- or -(OCF(CF 3 )CF 2 )d- is a group represented by the formula:

[0040] In the above formula (Rf-I-II), e and f are each independently an integer of preferably 5 to 200, more preferably 10 to 200. The sum of c, d, e and f is preferably 5 or more, more preferably 10 or more, and may be 15 or more, or 20 or more. The above formula (Rf-I-II) is preferably -(OCF 2 CF 2 CF 2 CF 2 )c-(OCF 2 CF 2 CF 2 )d-(OCF 2 CF 2 )e-(OCF 2 )f-, or -(OC 2 F 4 )e-(OCF 2 )f-, and more preferably -(OC 2 F 4 )e-(OCF 2 )f- is a group represented by the formula:

[0041] In the above formula (Rf-I-III), R 20 Preferably, OC 2 F 4 and R 21 Preferably, OC 2 F 4 , O.C. 3 F 6 and O.C. 4 F 8 or a combination of two or three groups independently selected from these groups, more preferably OC 3 F 6 and O.C. 4 F 8 is a group selected from the group consisting of OC 2 F 4 , O.C. 3 F 6 and O.C. 4 F 8 Examples of the combination of two or three groups independently selected from the group consisting of, but not limited to, -OC 2 F 4 O.C.3 F 6 -、-OC 2 F 4 OC 4 F 8 -、-OC 3 F 6 OC 2 F 4 -、-OC 3 F 6 OC 3 F 6 -、-OC 3 F 6 OC 4 F 8 -、-OC4F8OC 4 F 8 -、-OC 4 F 8 OC 3 F 6 -、-OC 4 F 8 OC 2 F 4 -、-OC 2 F 4 OC2F4OC 3 F 6 -、-OC 2 F 4 OC 2 F 4 OC 4 F 8 -、-OC 2 F 4 OC 3 F 6 OC2F4-、-OC 2 F 4 OC 3 F 6 OC 3 F 6 -、-OC 2 F 4 OC 4 F 8 OC 2 F 4 -、-OC 3 F 6 OC 2 F 4 OC 2 F 4 -、-OC 3 F 6 OC 2 F 4 OC 3 F6 -, -OC 3 F 6 OC3F6OC 2 F 4 - and -OC 4 F 8 O.C. 2 F 4 O.C. 2 F 4 --etc. In the above formula (Rf-I-III), g is preferably an integer of 3 or more, more preferably an integer of 5 or more. The above g is preferably an integer of 50 or less. In the above formula (Rf-I-III), OC 2 F 4 , O.C. 3 F 6 , O.C. 4 F 8 , O.C. 5 F 10 , and O.C. 6 F 12 may be either a straight chain or a branched chain, and is preferably a straight chain. In this embodiment, the above formula (Rf-I-III) is preferably -(OC 2 F 4 -OC 3 F 6 )g- or -(OC 2 F 4 -OC 4 F 8 )g-.

[0042] In the above formula (Rf-I-IV), e is preferably an integer of 1 to 100, more preferably an integer of 5 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example, 10 to 100.

[0043] In the above formula (Rf-IV), f is preferably an integer of 1 to 100, more preferably an integer of 5 to 100. The sum of a, b, c, d, e and f is preferably 5 or more, more preferably 10 or more, for example, 10 to 100.

[0044] In Rf, the ratio of e to f (hereinafter referred to as "e / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the e / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the e / f ratio, the more the lubricity is improved. On the other hand, by making the e / f ratio 0.5 or more, the stability of the compound can be further improved. The larger the e / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of the e / f ratio is preferably 0.8 or more.

[0045] Rf is represented by the following formula (Rf-I-VI): -(OCF 2 CF 2 CF 2 )a-(OCF(CF 3 )CF 2 )b-(OCF 2 CF(CF3))c-(OCF 2 CF 2 )d-(OCF(CF 3 ))e-(OCF 2 )f- (In the formula, a, b, c, d, e, and f each independently represent an integer of 0 to 200, the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeating unit with a, b, c, d, e, or f is arbitrary. The group may be represented by the following formula:

[0046] Rf is represented by the following formula (Rf-I-VII): -(OCF 2 CF 2 )d-(OCF(CF 3 ))e-(OCF 2 )f- (In the formula, d, e, and f each independently represent an integer of 0 to 200, the sum of d, e, and f is 1 or more, The order of the repeating units marked with d, e, or f is arbitrary. When Rf is this group, it is considered that the salt solubility becomes better because the number of ether bonds increases and the cations of the salt become more easily coordinated.

[0047] In Rf, the ratio of d to f (hereinafter referred to as "d / f ratio") may be 0.5 to 4, preferably 0.6 to 3, more preferably 0.7 to 2, and even more preferably 0.8 to 1.4. By making the d / f ratio 4 or less, the lubricity and chemical stability are further improved. The smaller the d / f ratio, the more the lubricity is improved. On the other hand, by making the d / f ratio 0.5 or more, the stability of the compound can be further improved. The larger the d / f ratio, the more the stability of the fluoropolyether structure is improved. In this case, the value of the d / f ratio is preferably 0.8 or more.

[0048] Each Rf is preferably independently a group represented by the above formula (Rf-II) or (Rf-I-II), and more preferably a group represented by the above formula (Rf-I-II).

[0049] The number average molecular weight of Rf is not particularly limited, but is, for example, 500 to 30,000, preferably 1,500 to 30,000, and more preferably 2,000 to 10,000. In this specification, the number average molecular weight of Rf is 19 This is a value measured by F-NMR.

[0050] R 1 ~R 3 The alkyl group and the fluoroalkyl group may be linear or branched, but are preferably linear. R 1 ~R 3 Examples of the aryl group include a phenyl group, a 4-nitrophenyl group, a 4-acetylaminophenyl group, and a 4-methanesulfonylphenyl group.

[0051] R 1 ~R 3are each independently preferably an alkyl group having 1 to 3 carbon atoms or a fluoroalkyl group having 1 to 3 carbon atoms, more preferably a methyl group, an ethyl group, a trifluoromethyl group or a pentafluoroethyl group, and further preferably a methyl group, a trifluoromethyl group or a pentafluoroethyl group.

[0052] R 4 The alkyl ester group may be linear or branched.

[0053] R 4 Examples of the substituent that the amido group or amino group may have include an alkyl group, an alkoxy group, and a hydroxy group.

[0054] R 4 are each preferably independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent, and more preferably a fluorine atom. R 4 is a fluorine atom, R 4 -Rb 4 and Rb 4 -R 4 , i.e., R 4 -Rf 1 and Rf 2 -R 4 are each independently -CF 3 , -CF 2 CF 3 , and -CF 2 CF 2 CF 3 It may be a group selected from the group consisting of:

[0055] The fluoropolyether is particularly preferably the fluoropolyether represented by the above formula (1) because it has good sheet strength and the like.

[0056] The above fluoropolyether is preferably liquid at any temperature between 25°C and 80°C in view of good sheet strength and the like. Examples of a form that is "liquid at any temperature between 25°C and 80°C" include a form that is solid at 25°C and liquid at 50°C, and a form that is solid at 50°C and liquid at 80°C. A form that is liquid at low temperatures and solid at high temperatures does not usually exist, and therefore is not included in the form that is "liquid at any temperature between 25°C and 80°C".

[0057] In the mixture for electrochemical devices of the present disclosure, the content of the fluoropolyether is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1.0 mass% or more, and is preferably 30 mass% or less, more preferably 20 mass% or less, even more preferably 15 mass% or less.

[0058] The fibrillary resin is a resin that easily fibrillates when a shear stress is applied, and examples thereof include liquid crystal polymer (LCP), cellulose, acrylic resin, ultra-high molecular weight polyethylene, polytetrafluoroethylene (PTFE), etc. These may be used alone or in combination of two or more. Among them, PTFE is preferred from the viewpoints of chemical stability, thermal stability, and processability.

[0059] The PTFE may be a homopolymer of tetrafluoroethylene (TFE), or may be a modified PTFE containing a polymerization unit based on TFE (TFE unit) and a polymerization unit based on a modified monomer (hereinafter also referred to as a "modified monomer unit"). The modified PTFE may contain 99.0% by mass or more of TFE units and 1.0% by mass or less of modified monomer units. The modified PTFE may be composed only of TFE units and modified monomer units. As the PTFE, the modified PTFE is preferred in that it improves the binding force, sheet strength and flexibility.

[0060] The modified PTFE preferably has a modified monomer unit content of 0.00001 to 1.0% by mass relative to the total polymerized units, in terms of improving the binding force, sheet strength, and flexibility. The lower limit of the modified monomer unit content is preferably 0.0001% by mass, more preferably 0.001% by mass, even more preferably 0.005% by mass, and even more preferably 0.010% by mass. The upper limit of the modified monomer unit content is preferably 0.90% by mass, more preferably 0.80% by mass, more preferably 0.50% by mass, even more preferably 0.40% by mass, and even more preferably 0.30% by mass. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0061] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0062] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene [CTFE], perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylenes, etc. The modified monomers used may be one type or multiple types.

[0063] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF 2 =CF-ORff(A) (wherein Rff represents a perfluoro organic group). In this specification, the "perfluoro organic group" refers to an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.

[0064] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) [PAVE], where Rff in the general formula (A) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0065] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0066] The perfluorovinyl ether further includes those in which, in the above general formula (A), Rff is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, and those in which Rff is the following formula:

[0067] [ka]

[0068] (wherein m represents 0 or an integer of 1 to 4), Rff is a group represented by the following formula:

[0069] [ka]

[0070] (wherein n represents an integer of 1 to 4).

[0071] The (perfluoroalkyl)ethylene [PFAE] is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE] and (perfluorohexyl)ethylene.

[0072] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF 2 =CF-CF 2 -ORff1 (B) (In the formula, Rff 1 represents a perfluoro organic group.

[0073] Rff 1 is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. 2 =CF-CF 2 -O-CF 3 , C.F. 2 =CF-CF 2 -OC 2 F 5 , C.F. 2 =CF-CF 2 -OC 3 F 7 , and CF 2 =CF-CF 2 -OC 4 F 9 At least one selected from the group consisting of CF 2 =CF-CF 2 -OC 2 F 5 , C.F. 2 =CF-CF 2 -OC 3 F 7 , and CF 2 =CF-CF 2 -OC 4 F 9 More preferably, at least one selected from the group consisting of CF 2 =CF-CF 2 -O-CF 2 CF 2 CF 3 is more preferred.

[0074] As the modified monomer, from the viewpoint of improving the extensibility, binding strength, and flexibility of the composite sheet, at least one selected from the group consisting of PAVE, HFP, VDF, and CTFE is preferable, and at least one selected from the group consisting of perfluoro(methyl vinyl ether) [PMVE], HFP, VDF, and CTFE is more preferable.

[0075] The PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-T-2005-527652 may be used.

[0076] Examples of PTFE that are commonly available on the market include F-104, F-106, F-107, F-104C, F-121, F-201, F-205, F-208, and F-302 manufactured by Daikin Industries, 60X, 601X, 602X, 605XTX, 613AX, 62X, 62NX, 62XTX, 640XTX, 641XTX, 650XTX, 669X, 669NX, 6CX, 6CNX, CFP6000X, 6J, 6CJ, 62J, 640J, and 641J manufactured by Chemours, and T manufactured by 3M. F2029, TF2025Z, TF2053Z, TF2073Z, TF2001Z, TF2071USZ, TF2072Z, etc., CD145, CD123, CD126E, CD097, CD084E, CD086EL, CD086EH, CD090E, CD122E, CD141E, CD127E, etc., manufactured by AGC, and DF681F, DF680F, DF330F, DF291F, DF230F, DF210F, DF132F, DF130F, DF120F, etc., manufactured by Solvay.

[0077] In terms of being able to form a composite sheet having even greater strength, the PTFE preferably has an endothermic peak temperature of 320° C. or higher, more preferably 325° C. or higher, even more preferably 330° C. or higher, even more preferably 335° C. or higher, even more preferably 340° C. or higher, even more preferably 342° C. or higher, and particularly preferably 344° C. or higher. The endothermic peak temperature is also preferably 350° C. or lower. The endothermic peak temperature is the temperature corresponding to the minimum point in the heat of fusion curve obtained by performing differential scanning calorimetry (DSC) at a heating rate of 10°C / min on PTFE that has no history of being heated to a temperature of 300°C or higher. When there are two or more minimum points in one melting peak, each of them is regarded as the endothermic peak temperature.

[0078] The above-mentioned PTFE preferably has one or more endothermic peaks in the range of 333 to 347°C in a heat of fusion curve when the temperature is increased at a rate of 10°C / min using a differential scanning calorimeter [DSC], and has a heat of fusion of 62 mJ / mg or more at 290 to 350°C calculated from the heat of fusion curve.

[0079] In the mixture for electrochemical devices of the present disclosure, the content of the fibrillar resin is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.5 mass% or more, and is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 3 mass% or less.

[0080] As the electrochemical device material, for example, an electrode active material can be used. That is, the mixture for electrochemical devices of the present disclosure may be an electrode mixture containing an electrode active material.

[0081] The electrode active material may be a positive electrode active material or a negative electrode active material.

[0082] The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release alkali metal ions, but for example, a material containing an alkali metal and at least one transition metal is preferable. Specific examples include an alkali metal-containing transition metal complex oxide and an alkali metal-containing transition metal phosphate compound. Among them, the positive electrode active material is preferably an alkali metal-containing transition metal complex oxide that produces high voltage. Examples of the alkali metal ion include lithium ion, sodium ion, potassium ion, etc., and lithium ion is preferable.

[0083] Examples of the alkali metal-containing transition metal composite oxide include: Formula:M a Mn 2-b M 1 b O 4 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0.9≦a; 0≦b≦1.5; M 1 is at least one metal selected from the group consisting of Fe, Co, Ni, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), Formula:MNi 1-c M 2 c O 2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦c≦0.5; M 2 is at least one metal selected from the group consisting of Fe, Co, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), or Formula:MCo 1-d M 3 d O 2 (Wherein, M is at least one metal selected from the group consisting of Li, Na, and K; 0≦d≦0.5; M 3 is at least one metal selected from the group consisting of Fe, Ni, Mn, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si and Ge), in which M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0084] Among these, MCoO is particularly popular because it can provide secondary batteries with high energy density and high output. 2 , M.M.N.O. 2 , MNiO 2 , M.M.n2 O 4 , M.N.I. 0.8 Mn 0.1 Co 0.1 O 2 , M.N.I. 0.8 Co 0.15 Al 0.05 O 2 , or MNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 etc. are preferred, and the compound represented by the following general formula is preferred. 0.8 Mn 0.1 Co 0.1 O 2 is particularly preferred. MNi h Co i Mn j M 5 k O 2 (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 5 represents at least one selected from the group consisting of Fe, Cu, Zn, Al, Sn, Cr, V, Ti, Mg, Ca, Sr, B, Ga, In, Si, and Ge, and (h+i+j+k)=1.0, 0≦h≦1.0, 0≦i≦1.0, 0≦j≦1.5, and 0≦k≦0.2.

[0085] The alkali metal-containing transition metal phosphate compound is, for example, a compound represented by the following general formula: M e M 4 f (PO 4 ) g (In the formula, M is at least one metal selected from the group consisting of Li, Na, and K, and M 4 represents at least one selected from the group consisting of V, Ti, Cr, Mn, Fe, Co, Ni and Cu, and 0.5≦e≦3, 1≦f≦2, 1≦g≦3. In the above, M is preferably one metal selected from the group consisting of Li, Na and K, more preferably Li or Na, and even more preferably Li.

[0086] The transition metal of the alkali metal-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, or the like. Specific examples include LiFePO 4 , Li 3 Fe 2 (PO 4 ) 3 , LifeP 2 O 7 Iron phosphates such as LiCoPO 4 and lithium transition metal phosphate compounds in which a part of the transition metal atoms constituting the main part of the lithium transition metal phosphate compounds is replaced with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc. As the lithium-containing transition metal phosphate compound, those having an olivine structure are preferred, and LiFePO 4 is particularly preferred.

[0087] Other examples of the positive electrode active material include lithium-nickel-based composite oxides. The lithium-nickel-based composite oxides are represented by the following general formula: Li y Ni 1-x M x O 2 (wherein x is 0.01≦x≦0.7, y is 0.9≦y≦2.0, and M is a metal atom (excluding Li and Ni)) is preferred.

[0088] Other positive electrode active materials include MFePO 4 , M.N.I. 0.8 Co 0.2 O 2 , M 1.2 Fe 0.4 Mn 0.4 O 2 , M.N.I. 0.5 Mn 1.5 O 2 , M.V. 3 O 6 , M 2 MnO 3 In particular, M 2 MnO 3, MNi 0.5 Mn 1.5 O 2 As for cathode active materials such as these, even when the secondary battery is operated at a voltage exceeding 4.4 V or at a voltage of 4.6 V or higher, they are preferable in that the crystal structure does not collapse. Therefore, an electrochemical device such as a secondary battery using a cathode material containing the cathode active material exemplified above is preferable because the remaining capacity hardly decreases even when stored at a high temperature, the resistance increase rate hardly changes, and the battery performance does not deteriorate even when operated at a high voltage.

[0089] As other cathode active materials, M 2 MnO 3 and MM 6 O 2 (wherein M is at least one metal selected from the group consisting of Li, Na, and K, and M 6 is a transition metal such as Co, Ni, Mn, Fe, etc.) and solid solution materials thereof can also be mentioned.

[0090] Examples of the solid solution material include, for example, an alkali metal manganese oxide represented by the general formula M x [Mn (1-y) M 7 y O z Here, M in the formula is at least one metal selected from the group consisting of Li, Na, and K, and M 7 consists of at least one metal element other than M and Mn, and includes, for example, one or more elements selected from the group consisting of Co, Ni, Fe, Ti, Mo, W, Cr, Zr, and Sn. Also, the values of x, y, and z in the formula are in the ranges of 1 < x < 2, 0 ≤ y < 1, and 1.5 < z < 3. Among them, Li 1.2 Mn 0.5 Co 0.14 Ni 0.14 O 2 such as Li 2 MnO 3 based on which LiNiO 2 or LiCoO 2 is solid-solved manganese-containing solid solution materials are preferable in that they can provide an alkali metal ion secondary battery having a high energy density.

[0091] In addition, it is preferable to include lithium phosphate in the positive electrode active material, since the continuous charging characteristics are improved. Although there is no limitation on the use of lithium phosphate, it is preferable to use the positive electrode active material and lithium phosphate mixed together. The amount of lithium phosphate used is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, with respect to the total of the positive electrode active material and lithium phosphate, and is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less.

[0092] In addition, a substance having a different composition may be attached to the surface of the positive electrode active material. Examples of the surface-attaching substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.

[0093] The positive electrode active material may be used alone or in any combination or ratio of two or more different compositions. In this case, a preferred combination is LiCoO 2 and LiNi 0.33 Co 0.33 Mn 0.33 O 2 Combination with ternary systems such as LiCoO 2 and LiMn 2 O 4 Or a combination of this Mn partially substituted with other transition metals, etc., or LiFePO 4 and LiCoO 2 Alternatively, a part of the Co may be replaced with another transition metal or the like.

[0094] The content of the positive electrode active material is preferably 50 to 90% by mass of the positive electrode mixture in terms of high battery capacity. The content in the positive electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit is preferably 88% by mass or less, more preferably 86% by mass or less. If the content of the positive electrode active material in the positive electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the ion conductivity, electronic conductivity, and electrode strength may be insufficient.

[0095] The negative electrode active material is not particularly limited, and examples thereof include carbonaceous materials such as lithium metal, artificial graphite, graphite carbon fiber, resin-sintered carbon, pyrolytic vapor-grown carbon, coke, mesocarbon microbeads (MCMB), furfuryl alcohol resin-sintered carbon, polyacene, pitch-based carbon fiber, vapor-grown carbon fiber, natural graphite, and non-graphitizable carbon; silicon-containing compounds such as silicon and silicon alloys; Li 4 Ti 5 O 12 Among them, those containing at least a carbonaceous material and silicon-containing compounds are particularly suitable.

[0096] The negative electrode active material used in the present disclosure preferably contains silicon as a constituent element. By using the negative electrode active material containing silicon as a constituent element, a high-capacity battery can be produced.

[0097] The silicon-containing material includes silicon particles, particles having a structure in which silicon particles are dispersed in a silicon-based compound, and silicon-based compounds having the general formula SiO x Silicon oxide particles represented by the formula (0.5≦x≦1.6) or a mixture thereof are preferred. By using these, a negative electrode mixture for a lithium ion secondary battery having a higher initial charge / discharge efficiency, a higher capacity, and excellent cycle characteristics can be obtained.

[0098] In the present disclosure, silicon oxide is a general term for amorphous silicon oxide. Silicon oxide before disproportionation has the general formula SiO x(0.5≦x≦1.6), where x is preferably 0.8≦x<1.6, and more preferably 0.8≦x<1.3. This silicon oxide can be obtained, for example, by heating a mixture of silicon dioxide and metallic silicon to produce silicon monoxide gas, and then cooling and precipitating the gas.

[0099] The content of the negative electrode active material is preferably 50 to 90% by mass of the negative electrode mixture in terms of high battery capacity. The content in the negative electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, and particularly preferably 75% by mass or more. The upper limit is preferably 88% by mass or less, more preferably 86% by mass or less. If the content of the negative electrode active material in the negative electrode active material layer is low, the electric capacity may be insufficient. Conversely, if the content is too high, the ionic conductivity, electronic conductivity, and electrode strength may be insufficient.

[0100] The electrochemical device material may be a solid electrolyte. That is, the mixture for electrochemical devices of the present disclosure may be a solid electrolyte mixture containing a solid electrolyte.

[0101] The solid electrolyte may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, when a sulfide-based solid electrolyte is used, it has the advantage of being flexible.

[0102] The sulfide-based solid electrolyte is not particularly limited, and may be Li 2 SP 2 S 5 , Li 2 SP 2 S 3 , Li 2 SP 2 S 3 -P 2 S 5 , Li 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , LiI-Li 2 SP 2 S 5 , LiI-Li 2 SP 2 O 5, LiI-Li 3 PO 4 -P 2 S 5 , LiI-Li 2 S-SiS 2 -P 2 S 5 , Li 2 S-SiS 2 -Li 4 SiO 4 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 3 P.S. 4 -Li 4 GeS 4 , Li 3.4 P 0.6 S 0.4 S 4 , Li 3.25 P 0.25 Ge 0.76 S 4 , Li 4-x Ge 1-x P x S 4 (x=0.6~0.8), Li 4+y Ge 1-y Ga y S 4 (y=0.2~0.3), LiPSCl, LiCl, Li 7-x-2y P.S. 6-x-y Cl x (0.8≦x≦1.7, 0 <y≦-0.25x+0.5)、Li 10 SnP 2 S 12 Any one selected from the above, or a mixture of two or more of them, can be used.

[0103] The sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.

[0104] In the mixture for electrochemical devices according to the present disclosure, the content of the solid electrolyte is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 40% by mass or more, and is preferably 99% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less.

[0105] The mixture for electrochemical devices according to the present disclosure may be an electrode mixture for a solid-state battery that contains an electrode active material and a solid electrolyte.

[0106] In the electrochemical device mixture of the present disclosure, the content of the electrochemical device material is preferably 70 mass % or more, more preferably 80 mass % or more, and even more preferably 90 mass % or more, and is preferably 99.5 mass % or less, more preferably 98.5 mass % or less, and even more preferably 97.5 mass % or less.

[0107] In the mixture for electrochemical devices of the present disclosure, the content of the polyalkylene oxide represented by the following formula (6) is preferably less than 20% by mass. This ensures good ionic conductivity. If it is 20% by mass or more, the viscosity of the composition increases, the ionic conductivity decreases, and at the same time, the electrochemical stability tends to decrease. (6)R 1B -(OCHR 1A (CH 2 )jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is an integer of 0 or 1 to 2, R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

[0108] In the mixture for electrochemical devices of the present disclosure, the content of the polyalkylene oxide represented by the above formula (6) is more preferably 10 mass % or less, further preferably 5 mass % or less, and particularly preferably 1 mass % or less. The lower limit is not particularly limited, and may be 0 mass %.

[0109] The mixture for electrochemical devices of the present disclosure may contain a lithium salt. By containing a lithium salt, the conductivity of lithium ions is improved.

[0110] Any lithium salt can be used as the lithium salt, and specific examples include the following: LiPF 6 , LiBF 4 , LiClO 4 , LiAlF 4 , LiSbF 6 , LiTaF 6 , LiWF 7 , LiAsF 6 , LiAlCl 4 , LiI, LiBr, LiCl, LiB 10 Cl 10 , Li 2 SiF 6 , Li 2 PFO 3 , LiPO 2 F 2 Inorganic lithium salts such as; LiWOF 5 Lithium tungstates such as: HCO 2 Li, C.H. 3 CO 2 Li, C.H. 2 FCO 2 Li, C.H.F. 2 CO 2 Li, C.F. 3 CO 2 Li, C.F. 3 CH 2 CO 2 Li, C.F. 3 CF 2 CO 2 Li, C.F. 3 CF 2 CF 2 CO 2 Li, C.F.3 CF 2 CF 2 CF 2 CO 2 Lithium carboxylates such as Li; FSO 3 Li, C.H. 3 SO 3 Li, C.H. 2 FSO 3 Li, C.H.F. 2 SO 3 Li, C.F. 3 SO 3 Li, C.F. 3 CF 2 SO 3 Li, C.F. 3 CF 2 CF 2 SO 3 Li, C.F. 3 CF 2 CF 2 CF 2 SO 3 Li, lithium methyl sulfate, lithium ethyl sulfate (C 2 H 5 OSO 3 Li), lithium salts having an S=O group such as lithium 2,2,2-trifluoroethyl sulfate; Lithium bis(trifluoromethanesulfonimide) (LiTFSI), Lithium bis(monofluorosulfonimide) (LiFSI), LiN(FCO) 2 , LiN(FCO)(FSO 2 ), LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2, lithium bisperfluoroethanesulfonylimide, lithium cyclic 1,2-perfluoroethanedisulfonylimide, lithium cyclic 1,3-perfluoropropanedisulfonylimide, lithium cyclic 1,2-ethanedisulfonylimide, lithium cyclic 1,3-propanedisulfonylimide, lithium cyclic 1,4-perfluorobutanedisulfonylimide, LiN(CF 3 SO 2 )(FSO 2 ), LiN(CF 3 SO 2 )(C 3 F 7 SO 2 ), LiN(CF 3 SO 2 )(C 4 F 9 SO 2 ), LiN(POF 2 ) 2 Lithium imide salts such as; LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 Lithium methide salts such as; Others, Formula: LiPF a (C n F 2n+1 ) 6-a (wherein a is an integer of 0 to 5, and n is an integer of 1 to 6) 3 (C 2 F 5 ) 3 , LiPF 3 (CF 3 ) 3 , LiPF 3 (iso-C 3 F 7 ) 3 , LiPF 5 (iso-C 3 F 7 ), LiPF 4 (CF 3 ) 2 , LiPF 4(C 2 F 5 ) 2 ), LiPF 4 (CF 3 SO 2 ) 2 , LiPF 4 (C 2 F 5 SO 2 ) 2 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiBF 3 C 3 F 7 , LiBF 2 (CF 3 ) 2 , LiBF 2 (C 2 F 5 ) 2 , LiBF 2 (CF 3 SO 2 ) 2 , LiBF 2 (C 2 F 5 SO 2 ) 2 Fluorine-containing organic lithium salts such as LiSCN and LiB(CN) 4 , LiB(C 6 H 5 ) 4 , Li 2 (C 2 O 4 ), LiP(C 2 O 4 ) 3 , Li 2 B 12 F b H 12-b (b is an integer of 0 to 3), etc.

[0111] Among them, LiTFSI, LiFSI, and LiPF 6 , LiBF 4 , LiSbF 6 , LiTaF 6 , LiPO 2 F 2 , FSO 3 Li, C.F.3 SO 3 Li, LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , Lithium cyclic 1,2-perfluoroethane disulfonylimide, Lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiPF 3 (CF 3 ) 3 , LiPF 3 (C 2 F 5 ) 3 LiTFSI, LiFSI, LiPF, etc. are preferred. 6 is particularly preferred.

[0112] These lithium salts may be used alone or in combination of two or more. A preferred example of a combination of two or more is LiPF 6 and LiBF 4 Use in combination with LiPF 6 And LiPO 2 F 2 , C 2 H 5 OSO 3 Li or FSO 3 When used in combination with Li, it has the effect of improving high-temperature storage characteristics, load characteristics, and cycle characteristics.

[0113] Another example is the combined use of an inorganic lithium salt and an organic lithium salt, which has the effect of suppressing deterioration due to storage at high temperatures. 3 SO 3 Li, LiN(FSO 2 ) 2 , LiN(FSO 2 )(CF 3 SO 2 ), LiN(CF 3 SO 2 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , Lithium cyclic 1,2-perfluoroethane disulfonylimide, Lithium cyclic 1,3-perfluoropropane disulfonylimide, LiC(FSO 2 ) 3 , LiC(CF 3 SO 2 ) 3 , LiC(C 2 F 5 SO 2 ) 3 , LiBF 3 CF 3 , LiBF 3 C 2 F 5 , LiPF 3 (CF 3 ) 3 , LiPF 3 (C 2 F 5 ) 3 etc. are preferred.

[0114] In the mixture for electrochemical devices of the present disclosure, the content of the lithium salt is preferably 0.1 mass % or more, more preferably 1 mass % or more, and preferably 30 mass % or less, more preferably 20 mass % or less.

[0115] The mixture for electrochemical devices according to the present disclosure may contain a conductive assistant. The conductive assistant is not particularly limited, but examples thereof include metal materials such as copper, nickel, and gold, graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, and carbon materials such as needle coke, carbon nanotubes, fullerene, and amorphous carbon such as VGCF, etc. These may be used alone or in any combination and ratio of two or more.

[0116] In the mixture for electrochemical devices of the present disclosure, the content of the conductive assistant is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, even more preferably 1 mass % or more, and is preferably 30 mass % or less, more preferably 15 mass % or less, even more preferably 5 mass % or less.

[0117] In the mixture for electrochemical devices of the present disclosure, the fibrillar resin acts as a binder, but may further contain other binders. The other binders are not particularly limited, but examples thereof include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, chitosan, alginic acid, polyacrylic acid, polyimide, cellulose, and nitrocellulose; rubber-like polymers such as SBR (styrene-butadiene rubber), isoprene rubber, butadiene rubber, fluororubber, NBR (acrylonitrile-butadiene rubber), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or hydrogenated products thereof; EPDM (ethylene-propylene Examples of such polymers include thermoplastic elastomer-like polymers such as styrene-ethylene-butadiene terpolymers, styrene-isoprene-styrene block copolymers, and hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride, vinylidene fluoride copolymers, and tetrafluoroethylene-ethylene copolymers; and polymer compositions having ionic conductivity for alkali metal ions (especially lithium ions). These may be used alone or in any combination and ratio of two or more.

[0118] In the mixture for electrochemical devices of the present disclosure, the content of the other binder is usually 0.01 to 3 mass %.

[0119] <Compound sheet for electrochemical devices> The mixture for electrochemical devices of the present disclosure is preferably in the form of a sheet. The present disclosure also relates to a mixture sheet for electrochemical devices, comprising the mixture for electrochemical devices of the present disclosure.

[0120] The thickness of the composite sheet for electrochemical devices of the present disclosure is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, even more preferably 180 μm or less, and particularly preferably 150 μm or less, and is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more.

[0121] The mixture sheet for electrochemical devices according to the present disclosure can be used as a solid electrolyte mixture sheet or an electrode mixture sheet.

[0122] <Method of manufacturing a composite sheet for electrochemical devices> The electrochemical device composite sheet of the present disclosure can be obtained, for example, by a production method including a step (1) of mixing a fluoropolyether, a fibrillar resin, and a material for electrochemical devices, and a step (2) of rolling the electrochemical device composite obtained in the step (1) into a sheet. The present disclosure also relates to such a method of manufacture.

[0123] The fluoropolyether, the fibrillar resin and the material for electrochemical devices in the above step (1) are the same as those explained in the mixture for electrochemical devices of the present disclosure.

[0124] In the above step (1), the mixing conditions are preferably 3000 rpm or less. The speed is preferably 10 rpm or more, more preferably 15 rpm or more, and even more preferably 20 rpm or more, and is preferably 2000 rpm or less, more preferably 1500 rpm or less, and even more preferably 1000 rpm or less. If the speed is below the above range, mixing will take a long time, which will affect productivity. If the speed is above the above range, fibrillation will proceed excessively, and the resulting mixture sheet may have poor strength and flexibility.

[0125] In the above step (1), the materials may be mixed and then molded into a bulk shape. Specific methods for molding into a bulk shape include extrusion molding, press molding, and the like. In addition, the "bulk shape" does not specify a particular shape, and may be in the form of a single mass, and includes shapes such as rods, sheets, spheres, and cubes.

[0126] Specific examples of the rolling method in the above step (2) include rolling methods using a roll press, a plate press, a calendar roll machine, or the like.

[0127] After the above step (2), a step (3) may be carried out in which a larger load is applied to the obtained rolled sheet to roll it into an even thinner sheet, or the step (3) may be carried out repeatedly. In this way, the rolled sheet is not thinned all at once, but is rolled little by little in stages, thereby improving flexibility. The number of times of step (3) is preferably 2 to 10 times, and more preferably 3 to 9 times. Specific rolling methods include, for example, a method in which two or more rolls are rotated and the rolled sheet is passed between them to process it into a thinner sheet.

[0128] It is also preferable to have a step (4) after the step (2) or the step (3) in which the rolled sheet is crushed, then formed into a bulk shape again, and rolled into a sheet. It is also preferable to repeat the step (4). The number of times of the step (4) is preferably 1 to 12 times, more preferably 2 to 11 times.

[0129] In the above step (4), specific methods for roughly crushing the rolled sheet and forming it into a bulk shape include a method of folding the sheet, a method of forming it into a rod or thin sheet shape, a method of chipping, etc. In this disclosure, "rough crushing" means changing the shape of the rolled sheet obtained in step (2) or step (3) into a different shape in order to roll it into a sheet shape in the next step, and also includes the case where the rolled sheet is simply folded.

[0130] Furthermore, the step (4) may be followed by the step (3) or may be repeated. Furthermore, uniaxial or biaxial stretching may be performed in the steps (2), (3) and (4).

[0131] In the above steps (2), (3), and (4), the rolling ratio is preferably 10% or more, more preferably 20% or more, and is preferably 80% or less, more preferably 65% ​​or less, and even more preferably 50% or less. If it is below the above range, the number of times of rolling increases, which takes time and affects productivity. If it is above the above range, fibrillation may proceed excessively, resulting in a composite sheet with poor strength and flexibility. The rolling ratio here refers to the reduction rate of the thickness of the sample after processing relative to the thickness before rolling. The sample before rolling may be a bulk-shaped raw material composition or a sheet-shaped raw material composition. The thickness of the sample refers to the thickness in the direction in which a load is applied during rolling.

[0132] <Electrochemical devices> The present disclosure also relates to an electrochemical device using the mixture sheet for electrochemical devices of the present disclosure.

[0133] The electrochemical device of the present disclosure may use the mixture sheet for electrochemical devices of the present disclosure as an electrode mixture sheet, may use the mixture sheet for electrochemical devices of the present disclosure as a solid electrolyte mixture sheet, or may use the mixture sheet as an electrode mixture sheet and a solid electrolyte mixture sheet.

[0134] The electrochemical device of the present disclosure preferably comprises a positive electrode, a negative electrode, etc., and more specifically, is preferably a secondary battery comprising these, and is particularly preferably a lithium ion secondary battery.

[0135] The positive electrode is preferably composed of a current collector and an electrode mixture sheet containing the positive electrode active material. The material of the positive electrode current collector includes metals such as aluminum, titanium, tantalum, stainless steel, nickel, and the like, and metal materials such as alloys thereof; carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly aluminum or its alloys, are preferred.

[0136] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0137] In addition, it is also preferable that the surface of the current collector is coated with a conductive assistant from the viewpoint of reducing the electrical contact resistance between the current collector and the positive electrode active material layer. Examples of the conductive assistant include carbon and precious metals such as gold, platinum, and silver.

[0138] The positive electrode may be manufactured by a conventional method, for example, a method in which an electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0139] The density of the positive electrode mixture sheet is preferably 2.80 g / cm 3 More preferably, 3.00 g / cm 3 More preferably, 3.20 g / cm 3 or more, and preferably 3.80 g / cm 3 Less than or equal to 3.75 g / cm 3 More preferably, 3.70 g / cm 3The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current densities, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.

[0140] The negative electrode is preferably composed of a current collector and an electrode mixture sheet containing the negative electrode active material. The material of the current collector for the negative electrode includes metals such as copper, nickel, titanium, tantalum, and stainless steel, or metal materials such as alloys thereof; and carbon materials such as carbon cloth and carbon paper. Among them, metal materials, particularly copper, nickel, or alloys thereof, are preferred.

[0141] The shape of the current collector may be metal foil, metal cylinder, metal coil, metal plate, expanded metal, punched metal, foam metal, etc. in the case of metal materials, and carbon plate, carbon thin film, carbon cylinder, etc. in the case of carbon materials. Among these, metal foil is preferred. The metal foil may be appropriately formed into a mesh shape. The thickness of the metal foil is optional, but is usually 1 μm or more, preferably 3 μm or more, more preferably 5 μm or more, and usually 1 mm or less, preferably 100 μm or less, more preferably 50 μm or less. If the metal foil is thinner than this range, the strength required as a current collector may be insufficient. Conversely, if the metal foil is thicker than this range, the handling may be impaired.

[0142] The negative electrode may be produced by a conventional method, for example, a method in which the above-mentioned electrode mixture sheet and a current collector are laminated with an adhesive therebetween, and then vacuum dried.

[0143] The density of the negative electrode mixture is preferably 1.3 g / cm 3 More preferably, 1.4 g / cm 3 More preferably, 1.5 g / cm 3 More preferably, it is 2.0 g / cm 3 Less than or equal to 1.9 g / cm 3 More preferably, 1.8 g / cm 3The range is as follows. If the range is exceeded, the permeability of the electrolyte to the vicinity of the current collector / active material interface will decrease, and the charge / discharge characteristics, especially at high current densities, will decrease, and high output may not be obtained. If the range is exceeded, the conductivity between the active materials will decrease, and the battery resistance will increase, and high output may not be obtained.

[0144] The secondary battery may be a secondary battery that uses an electrolyte solution, or may be a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.

[0145] The secondary battery using the above-mentioned electrolyte may use electrolytes, separators, etc. that are used in known secondary batteries. These will be described in detail below.

[0146] The electrolyte is preferably a non-aqueous electrolyte, which may be prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts.

[0147] The organic solvent for dissolving the electrolyte salt is not particularly limited, and one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorinated carbonates can be used.

[0148] As the electrolyte salt, the above-mentioned lithium salt can be used.

[0149] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L or less.

[0150] The secondary battery using the above-mentioned electrolyte preferably further includes a separator. The material and shape of the separator are not particularly limited as long as they are stable to the electrolyte and have excellent liquid retention, and any known separator can be used. Among them, it is preferable to use a material formed of a material stable to the electrolyte, such as a resin, glass fiber, or inorganic material, and to use a porous sheet or nonwoven fabric having excellent liquid retention.

[0151] Examples of materials that can be used for the resin and glass fiber separator include polyolefins such as polyethylene and polypropylene, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, and glass filters. These materials may be used alone or in any combination and ratio, such as polypropylene / polyethylene two-layer film and polypropylene / polyethylene / polypropylene three-layer film. Among these, the separator is preferably a porous sheet or nonwoven fabric made of polyolefins such as polyethylene and polypropylene, because of its excellent electrolyte permeability and shutdown effect.

[0152] The thickness of the separator is arbitrary, but is usually 1 μm or more, preferably 5 μm or more, more preferably 8 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is thinner than the above range, the insulating properties and mechanical strength may be reduced. If the separator is thicker than the above range, not only may the battery performance such as rate characteristics be reduced, but also the energy density of the entire electrolyte battery may be reduced.

[0153] On the other hand, examples of inorganic materials that can be used include oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate, and these are in particulate or fibrous form.

[0154] As for the form, a thin film such as a nonwoven fabric, a woven fabric, or a microporous film is used. In the thin film form, a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm is preferably used. In addition to the above independent thin film form, a separator can be used in which a composite porous layer containing the above inorganic particles is formed on the surface layer of a positive electrode and / or a negative electrode using a resin binder. For example, a porous layer can be formed on both sides of a positive electrode using alumina particles with a 90% particle size of less than 1 μm and a fibrillated resin as a binder.

[0155] The material of the exterior case is not particularly limited as long as it is a material that is stable against the electrolyte used. Specifically, metals such as nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminate film of resin and aluminum foil (laminate film) are used. From the viewpoint of weight reduction, metals such as aluminum or aluminum alloy, and laminate films are preferably used.

[0156] In the case of an exterior case using metals, there are cases in which the metals are welded together by laser welding, resistance welding, or ultrasonic welding to form a sealed structure, or cases in which the metals are used via a resin gasket to form a crimped structure. In the case of an exterior case using the laminate film, there are cases in which the resin layers are heat-sealed together to form a sealed structure. In order to improve the sealing property, a resin different from the resin used in the laminate film may be interposed between the resin layers. In particular, when the resin layer is heat-sealed via a current collecting terminal to form a sealed structure, the joining between the metal and the resin is performed, so that a resin having a polar group or a modified resin into which a polar group has been introduced is preferably used as the interposed resin.

[0157] The shape of the secondary battery using the above-mentioned electrolyte solution is arbitrary, and examples of the shape include a cylindrical shape, a square shape, a laminated shape, a coin shape, a large shape, etc. The shapes and configurations of the positive electrode, the negative electrode, and the separator can be changed according to the shape of each battery.

[0158] The solid-state secondary battery is preferably an all-solid-state secondary battery. The solid-state secondary battery is preferably a lithium ion battery, and is also preferably a sulfide-based all-solid-state secondary battery.

[0159] The solid secondary battery preferably includes a positive electrode, a negative electrode, and a solid electrolyte layer interposed between the positive electrode and the negative electrode.

[0160] The solid secondary battery may include a separator between the positive electrode and the negative electrode. Examples of the separator include porous membranes such as polyethylene and polypropylene, and nonwoven fabrics such as nonwoven fabrics made of resins such as polypropylene and nonwoven fabrics made of glass fibers.

[0161] The solid secondary battery may further include a battery case. The shape of the battery case is not particularly limited as long as it can accommodate the above-mentioned positive electrode, negative electrode, solid electrolyte layer, etc., but specific examples include a cylindrical type, a square type, a coin type, a laminate type, etc.

[0162] The solid secondary battery can be produced, for example, by stacking a positive electrode, a solid electrolyte layer sheet, and a negative electrode in this order and pressing them.

[0163] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0164] Next, the present disclosure will be described with reference to examples, but the present disclosure is not limited to these examples.

[0165] The following compounds were used: Compounds 1-1 to 1-7 were liquids at 25°C. <Compound 1-1> CH 3 O(CH 2 CH 2 O) x1 CH 2 CF 2(OCF 2 CF 2 ) y (OCF 2 ) z OCF 2 CH 2 O(CH 2 CH 2 O) x2 CH 3 (x1:4, y: average 12.3, z: average 10.2, x2:4, (CH 2 CH 2 Number average molecular weight of (CH 2 CH 2 O) x2 Number average molecular weight: 176) <Compound 1-2> Compound with the same structure as compound 1-1 (x1: average 8.4, y: average 12.3, z: average 10.2, x2: average 8.4, (CH 2 CH 2 O) x1 Number average molecular weight: 400, (CH 2 CH 2 O) x2 Number average molecular weight: 400) <Compound 1-3> CF 2 (CF 3 )CF 2 (OCF(CF 3 )CF 2 ) x OCF(CF 3 )CH 2 O(CH 2 CH 2 O) y CH 3 (x: average 9.4, y: 4, (CH 2 CH 2 O) y Number average molecular weight: 176) <Compound 1-4> Compounds with the same structure as Compound 1-3 (x: average 14.3, y: 4, (CH 2 CH 2 O) y Number average molecular weight: 176) <Compound 1-5> Fluorolink E10H (Solvay) HO(CH 2 CH 2 O) x1 CH 2 CF 2 O(CF 2 CF 2 O) x2 (CF 2 O) y CF 2 CH 2 O(CH 2 CH 2 O) x3 H (x1: average 1.27, y: average 8.16, x2: average 7.09, x3: average 1.27) <Compound 1-6> CF 3 CF 2 (OCF 2 CF 2 ) x1 (OCF 2 ) y1 OCF 2 CH 2 O(CH 2 CH 2 O) z CH 2 CF 2 (OCF 2 CF 2 ) x2 (OCF 2 ) y2 OCF 2 CF 3 (x1: average 15.5, y1: average 13.0, z: average 4.1, x2: average 15.5, y2: average 13.0, (CH 2 CH 2 O) z Number average molecular weight: 200) <Compound 1-7> A compound having a chemical structure represented by the following formula (I) (m: average 29.5, n: average 24.6, terminal R is CF 3 and CF 2 CF 3 The number average molecular weight is 5120, which exists in an average ratio of 1:0.17.

[0166] [ka]

[0167] <Compound 2-1> Ethyl methyl carbonate (EMC, Kishida Chemical Co., Ltd.) <Compound 2-2> Polyethylene glycol 200 (Tokyo Chemical Industry Co., Ltd.)

[0168] (Synthesis Example 1) Synthesis of Compound 1-1 In a nitrogen-substituted reaction vessel, 600 mg of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 15.3 mmol), 30 g of 1,3-bis(trifluoromethyl)benzene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 10 g of fluoropolyether both-terminal alcohol (manufactured by Solvay, Fomblin D2, 5.1 mmol) were added and heated and stirred at 70 ° C for 3 hours. The internal temperature was raised to 65 ° C, and 5.5 g of triethylene glycol-2-bromoethyl methyl ether (manufactured by Tokyo Chemical Industry Co., Ltd., 20.4 mmol) was dropped from the dropping funnel over 10 minutes, and the mixture was heated and stirred for 6 hours. After returning to room temperature, 5 ml of 1N hydrochloric acid was added to the reaction solution and stirred for 3 hours. This solution was washed four times with pure water, and 2 g of magnesium sulfate was added to the separated organic layer and dried. The volatile matter was removed from the treated solution from which magnesium sulfate had been removed by filtration, and the solution was further dried at 100 ° C for 3 hours to obtain compound 1-1.

[0169] (Synthesis Example 2) Synthesis of tosylated polyethylene glycol monomethyl ether In a nitrogen-substituted reaction vessel, 8.0 g of polyethylene glycol monomethyl ether 400 (Tokyo Chemical Industry Co., Ltd., average molecular weight 380-420, 20.0 mmol), 25 mL of tetrahydrofuran (Tokyo Chemical Industry Co., Ltd.), and 4.7 g of p-toluenesulfonyl chloride (Tokyo Chemical Industry Co., Ltd., 25 mmol) were added and stirred until homogenous. A solution of 3.4 g of potassium hydroxide (FUJIFILM Wako Pure Chemical Industries, Ltd., 60 mmol) / 10 mL of pure water was added to a reaction vessel in an ice water bath, and after stirring for 10 minutes, the ice water bath was removed and the mixture was stirred at room temperature for 12 hours. The reaction solution was poured into a mixture of 30 mL of ice water / 60 mL of methylene chloride, and the aqueous layer was extracted three times with methylene chloride. 8 g of magnesium sulfate was added to the separated organic layer and dried. Volatiles were removed from the treated solution from which magnesium sulfate had been removed by filtration, and a tosylated polyethylene glycol monomethyl ether was obtained.

[0170] (Synthesis Example 3) Synthesis of Compound 1-2 Compound 1-2 was obtained by reacting the tosylated polyethylene glycol monomethyl ether synthesized in Synthesis Example 2 under the reaction conditions of Synthesis Example 1, instead of triethylene glycol-2-bromoethyl methyl ether.

[0171] (Synthesis Example 4) Synthesis of Compound 1-3 In a nitrogen-substituted reaction vessel, 600 mg of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 15.3 mmol), 30 g of 1,3-bis(trifluoromethyl)benzene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 10.2 g of fluoropolyether one-terminated alcohol (manufactured by Unichem Co., Ltd., perfluoropolyether modified, molecular weight 2000, 5.1 mmol) were added and heated and stirred at 70 ° C for 3 hours. The internal temperature was raised to 65 ° C, and 2.8 g of triethylene glycol-2-bromoethyl methyl ether (manufactured by Tokyo Chemical Industry Co., Ltd., 10.0 mmol) was dropped from the dropping funnel over 10 minutes, and the mixture was heated and stirred for 6 hours. After returning to room temperature, 5 ml of 1N hydrochloric acid was added to the reaction solution and stirred for 3 hours. This solution was washed four times with pure water, and 2 g of magnesium sulfate was added to the separated organic layer and dried. The magnesium sulfate was removed by filtration, and the volatile matter was distilled off from the treated solution. The solution was then dried at 100°C for 3 hours to obtain compound 1-3.

[0172] (Synthesis Example 5) Synthesis of Compound 1-4 Compound 1-4 was obtained by carrying out the same reaction as in Synthesis Example 4, except that the fluoropolyether one-terminated alcohol was replaced with a perfluoropolyether modified product having a molecular weight of 3,000, manufactured by Unichem Co., Ltd.

[0173] (Synthesis Example 6) Synthesis of Compound 1-6 In a nitrogen-substituted reaction vessel, 600 mg of sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 15.3 mmol), 30 g of 1,3-bis(trifluoromethyl)benzene (manufactured by Tokyo Chemical Industry Co., Ltd.), and 20.4 g of fluoropolyether one-terminated alcohol (manufactured by Solvay, Fluorolink ZMF-402, 5.1 mmol) were added and heated and stirred at 70 ° C for 3 hours. The internal temperature was set to 65 ° C, and 1.3 g (2.5 mmol) of the polyethylene glycol both-terminated tosylated body obtained in Synthesis Example 9 was dissolved in 5 g of 1,3-bis(trifluoromethyl)benzene and dropped from the dropping funnel over 10 minutes, and the mixture was heated and stirred for 6 hours. After returning to room temperature, 5 ml of 1N hydrochloric acid was added to the reaction solution and stirred for 3 hours. This solution was washed four times with pure water, and 2 g of magnesium sulfate was added to the separated organic layer and dried. The magnesium sulfate was removed by filtration, and the volatile matter was distilled off from the treated solution. The solution was then dried at 100°C for 3 hours to obtain compound 1-6.

[0174] PTFE-1 to PTFE-3 were prepared and analyzed by the following method.

[0175] <Average primary particle diameter> The PTFE aqueous dispersion was diluted with water until the solid content became 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average primary particle diameter determined by measuring the unidirectional diameter using a transmission electron microscope were measured to prepare a calibration curve. Using this calibration curve, the average primary particle diameter was determined from the measured transmittance of the 550 nm projected light for each sample.

[0176] <Polymer solids concentration> 1 g of the PTFE aqueous dispersion is dried in a blower dryer at 150° C. for 60 minutes, and the ratio of the mass of the heating residue to the mass (1 g) of the aqueous dispersion is expressed as a percentage and used.

[0177] <Modified monomer content> The CTFE content was determined by press-molding PTFE powder to produce a thin film disk, and measuring the infrared absorbance of the thin film disk using FT-IR. -1 Absorbance at / 2360cm-1 The absorbance ratio was calculated by multiplying the absorbance ratio at The HFP content was determined by press-molding the PTFE composition to produce a thin-film disk, measuring the infrared absorbance of the thin-film disk using FT-IR, and determining the HFP content at 982 cm -1 Absorbance at / 935cm -1 The absorbance ratio was calculated by multiplying the absorbance ratio at

[0178] <Standard specific gravity (SSG)> Using samples molded in accordance with ASTM D4895 89, the measurement was performed by the water displacement method in accordance with ASTM D 792.

[0179] A white solid A was obtained by the method described in Synthesis Example 1 of WO 2021 / 045228.

[0180] (Example 1) In a 6-liter stainless steel autoclave equipped with a stirring blade and a temperature control jacket, 3480 g of deionized water, 100 g of paraffin wax, and 5.3 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was kept at 70 ° C. while stirring. Next, an aqueous solution of 15.0 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 400 g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0 mg of hydroquinone dissolved in 20 g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerized reached about 1200 g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 310 nm, and the solid content concentration was 25.3 mass%.

[0181] The resulting PTFE aqueous dispersion was diluted to a solids concentration of 13% by mass, and the PTFE was coagulated while stirring in a container, and then the mixture was filtered to separate the water, thereby obtaining a wet PTFE powder. The obtained wet PTFE powder was dried at 180° C. for 18 hours to obtain PTFE-1. The SSG of the obtained PTFE-1 was 2.156.

[0182] (Example 2) In a 6-liter stainless steel autoclave equipped with a stirring blade and a temperature control jacket, 3580 g of deionized water, 100 g of paraffin wax, and 5.4 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 80 ° C. to remove oxygen. After adding 1.20 g of CTFE, TFE was further injected to make the system pressure 0.78 MPaG, and the system temperature was maintained at 80 ° C. while stirring. Next, an aqueous solution of 360 mg of disuccinic acid peroxide dissolved in 20 g of water and an aqueous solution of 10 mg of ammonium persulfate dissolved in 20 g of water were injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the pressure in the system decreased, but TFE was added to maintain the system temperature at 80 ° C. and the system pressure at 0.78 MPaG. When 1530 g of TFE was consumed from the start of polymerization (conversion rate 90%), 4.2 g of CTFE was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerization reached about 1700 g from the start of polymerization, the stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average primary particle size of the obtained aqueous PTFE dispersion was 241 nm, and the solid content was 32.0 mass%.

[0183] The resulting PTFE aqueous dispersion was diluted to a solids concentration of 13% by mass, and the mixture was vigorously stirred in a vessel equipped with a stirrer to cause solidification, and then filtered to separate the water, thereby obtaining a wet PTFE powder. The obtained wet PTFE powder was dried at 145°C for 18 hours to obtain PTFE-2. The CTFE content of the obtained PTFE-2 was 0.23 mass %, and the SSG was 2.170.

[0184] (Preparation Example 1) 0.273 g of lauric acid was added to 16 g of deionized water, and 2.77 g of a 2.8% aqueous solution of ammonia was gradually added thereto while stirring, to obtain an aqueous solution C. 10 g of lauric acid was added to 100 g of deionized water, and 25 g of a 10% aqueous solution of ammonia was gradually added while stirring to obtain an aqueous solution D. The pH at this time was 9.6.

[0185] (Preparation Example 3) In a 3-liter stainless steel autoclave equipped with a stirring blade and a temperature control jacket, 1748 g of deionized water, 90 g of paraffin wax, the aqueous solution C obtained in Preparation Example 1, and 0.5 g of ammonium oxalate were added. The pH of the aqueous dispersion at this time was 9.0. The autoclave was sealed and heated to 70°C, and the system was replaced with nitrogen to remove oxygen. While stirring, the temperature in the system was kept at 70°C, 2.0 g of HFP was added, and the pressure was increased with TFE to 2.70 MPaG. When a 0.5% by mass aqueous potassium permanganate solution was continuously charged into the autoclave as a polymerization initiator, a drop in pressure occurred and the reaction began. TFE was charged so that the system pressure was constant at 2.70 MPaG. When 80 g of TFE was charged, stirring was stopped, and the system was depressurized until the pressure in the system reached atmospheric pressure. Immediately, the autoclave was filled with TFE, the system pressure was set to 2.70 MPaG, and stirring was resumed to continue the reaction. At the same time, the aqueous solution D obtained in Preparation Example 1 was continuously charged into the autoclave. When 680 g of TFE was charged, stirring was stopped, and the system was depressurized until atmospheric pressure was reached. By the end of the reaction, 56.0 g of an aqueous potassium permanganate solution and 26.2 g of an aqueous solution D were charged. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The pH of the obtained aqueous PTFE dispersion was 8.8, the solid content was 27.1 mass%, and the primary particle size was 220 nm.

[0186] The resulting PTFE aqueous dispersion was diluted with deionized water to a solids concentration of 13% by mass, and the mixture was stirred vigorously in a container equipped with a stirrer to cause solidification, and then filtered to separate the water, thereby obtaining a wet powder. The obtained wet powder was dried at 240° C. for 18 hours to obtain PTFE-3. The resulting PTFE-3 had an HFP content of 0.002% by mass and a standard specific gravity of 2.170.

[0187] The preparation of mixture sheets in the examples and comparative examples, evaluation of the mixture sheets, and evaluation of the batteries were carried out according to the following procedures. (Preparation of positive electrode mixture sheet) The active material and the conductive additive were weighed, charged into a V-type mixer, and mixed at 37 rpm for 10 minutes to obtain a mixture of the active material and the conductive additive. Next, the mixture and a compound (any of compounds 1-1 to 1-7, 2-1, or 2-2) were added to a high-speed fluid mixer and processed at 200 rpm for 1 minute to disperse the mixture. Then, a weighed amount of binder (fibrillar resin: PTFE powder) was added to the mixture, and it was thoroughly cooled in a thermostatic chamber at 5° C. The mixture consisting of the active material, conductive assistant, binder, and compound was added to a high-speed fluid mixer, and the mixture was homogenized by processing at 1500 rpm for 3 minutes. Thereafter, the mixture was sufficiently heated in a thermostatic bath at 80° C., and then treated in a high-speed fluid mixer at 2500 rpm for 8 minutes to promote fibrillation, thereby obtaining an electrode mixture. The electrode mixture was fed into a rolling machine in which metal rolls were arranged in parallel and capable of rotating at different peripheral speeds, to obtain an electrode mixture sheet (temperature: 60° C., left roll rotation speed: 1 m / min, right roll rotation speed: 0.8 m / min). The obtained mixture sheet was again put into the rolling machine and rolled to obtain an electrode mixture sheet having a stronger sheet strength. Thereafter, the electrode mixture sheet was placed in a roll press machine and the gap was adjusted to a final thickness of 80 μm. Table 1 shows the material types and composition ratios (mass ratios). Moreover, all of the obtained electrode mixture sheets were self-supporting films.

[0188] (Measurement of the strength of the positive electrode mixture sheet) The positive electrode mixture sheet was cut out to prepare a rectangular test piece with a width of 4 mm. A tensile tester (Shimadzu Corporation AGS-100NX) was used to measure at 100 mm / min. The chuck distance was 40 mm. Displacement was applied until breakage, and the maximum stress of the measured results was taken as the strength of each sample. Comparative Example A-1 was compared as 100 in Table 2, Comparative Example B-1 in Table 3, and Comparative Example C-1 in Table 4. The samples were ranked from A to E, with the highest tensile strength and the best electrode strength. A: 150 or more B:130~149 C:110~129 D:95~109 E: Less than 95

[0189] (Preparation of positive electrode) The above positive electrode mixture sheet was adhered to 20 μm aluminum foil as follows. The adhesive used was a slurry of polyvinylidene fluoride (PVDF) dissolved in N-methylpyrrolidone (NMP) and carbon black dispersed in a ratio of 80:20. The adhesive was applied to aluminum foil and dried on a hot plate at 120°C for 15 minutes to form a current collector with an adhesive layer. Thereafter, the positive electrode mixture sheet was placed on a collector with an adhesive layer, and the positive electrode mixture sheet and the collector were bonded together using a roll press machine heated to 100°C. The sheet was then cut to the desired size and tabbed to form a positive electrode.

[0190] (Preparation of negative electrode) 98 parts by mass of carbonaceous material (graphite) was mixed with 1 part by mass of aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) and 1 part by mass of aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 50% by mass) as a thickener and binder, and the mixture was mixed with a disperser to form a slurry. The obtained slurry was applied to a copper foil having a thickness of 10 μm, dried, and rolled with a press machine, cut to the desired size, and tabbed to form a negative electrode.

[0191] (Preparation of electrolyte) A mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (EC:EMC = 30:70 (volume ratio)) was weighed into a sample bottle as an organic solvent, and fluoroethylene carbonate (FEC) and vinylene carbonate (VC) were dissolved in it at 1 mass% each to prepare a mixed solution. LiPF 6 The salts were mixed at 23° C. to obtain a non-aqueous electrolyte.

[0192] (Preparation of aluminum laminated cell) The positive electrode was placed opposite to the negative electrode via a 20 μm-thick microporous polyethylene film (separator), and the nonaqueous electrolyte obtained above was poured into the positive electrode. After the nonaqueous electrolyte had sufficiently permeated the separator and the like, the positive electrode was sealed, precharged, and aged to prepare a lithium ion secondary battery.

[0193] <Battery evaluation> The lithium ion secondary battery produced above was charged at a constant current / constant voltage (hereinafter referred to as CC / CV charging) at 45° C. with a current equivalent to 0.33 C (0.1 C cut) up to 4.25 V, and then discharged at a constant current of 0.33 C down to 3 V. This was counted as one cycle, and the initial discharge capacity was calculated from the discharge capacity at the third cycle. The initial discharge capacity (initial capacity) thus obtained was ranked by relative evaluation. Comparative Example A-1 in Table 2, Comparative Example B-1 in Table 3, and Comparative Example C-1 in Table 4 were set as 100 for comparison. ◎: 110 or more ○:105~109 △:95~104 ×: Less than 95 Next, the batteries for which the evaluation of the initial discharge capacity had been completed were again CC / CV charged (0.1C cut) at 45°C to 4.3V, and the volume of the batteries was determined by the Archimedes method. After determining the volume of the batteries, they were stored at high temperature at 60°C for 30 days. After the high temperature storage was completed, the batteries were sufficiently cooled and then the volume of the batteries was determined at 25°C, and the amount of gas generated was calculated from the difference in volume of the batteries before and after the storage test. The gas generation amounts were ranked by relative evaluation. Comparative Example A-1 was set as 100 in Table 2, Comparative Example B-1 in Table 3, and Comparative Example C-1 in Table 4. ◎: Less than 80 ○:80~89 △:90~109 ×:110 or more

[0194] [Table 1]

[0195] [Table 2]

[0196] [Table 3]

[0197] [Table 4]

Claims

1. A mixture for electrochemical devices comprising a fluoropolyether, a fibrillar resin and an electrochemical device material.

2. 2. The mixture for electrochemical devices according to claim 1, wherein the fluoropolyether is at least one of the fluoropolyethers represented by the following formulas (1) to (4): (1) R 1 -O-Ra 1 -Rb 1 -O-Ra 1 -R 1 (2) R 2 -Rb 2 -O-Ra 2 -Rb 2 -R 2 (3) R 3 -Rb 3 -O-Ra 3 -R 3 (4)R 4 -Rb 4 -R 4 (In the formula, Ra 1 ~Ra 3 are each independently a polyoxyalkylene group containing 4 to 50 oxyalkylene units not containing fluorine, Ra 1 ~Ra 3 Each oxyalkylene unit is independently —CH 2 CH 2 O- or -CH 2 CH(J)O-, Each J is independently an alkyl group or an aryl group; Rb 1 ~Rb 4 are each independently a fluoropolyether group represented by the following formula (5): R 1 ~R 3 each independently represents a hydrogen atom, a hydroxyl group, a fluorine atom, an alkyl group having 1 to 3 carbon atoms, an aryl group, a carboxylic acid group, or a fluoroalkyl group having 1 to 3 carbon atoms, R 4 are each independently a fluorine atom, a hydrogen atom, a hydroxyl group, an aldehyde group, a carboxylic acid group, an alkyl ester group having 1 to 10 carbon atoms, an amide group which may have a substituent, or an amino group which may have a substituent. (5)-Rf 1 -Rf-O-Rf 2 - (wherein, Rf 1 and Rf 2 each independently represents an alkylene group having 1 to 16 carbon atoms which may be substituted by a fluorine atom, Rf is a divalent fluoropolyether group.

3. The Ra 1 ~Ra 3 each independently represents a polyoxyalkylene group represented by the following formula (Ra-I): (Ra-I): -(CH 2 CH 2 O)r(CH 2 CH(CH 3 )O)s(CH 2 CH(CH 2 CH 3 )O)t(CH 2 CH(Ph)O)u- (In the formula, r, s, t, and u are each independently 0 or an integer of 1 or more, and r+s+t+u is 4 to 50.)

4. The Ra 1 ~Ra 3 The mixture for electrochemical devices according to claim 2 or 3, wherein the number average molecular weight of is 40 to 4,000.

5. 4. The mixture for electrochemical devices according to claim 2, wherein each Rf is independently a fluoropolyether group represented by the following formula (Rf-I): Formula (Rf-I): -(OC 6 F 12 )a-(OC 5 F 10 )b-(OC 4 F 8 )c-(OC 3 Rc 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, each Rc is independently a hydrogen atom, a fluorine atom, or a chlorine atom, a, b, c, d, e, and f each independently represent an integer from 0 to 200; the sum of a, b, c, d, e, and f is greater than or equal to 1; The order of each repeating unit to which a, b, c, d, e, or f is assigned is arbitrary; When all Rc's are hydrogen atoms or chlorine atoms, at least one of a, b, c, e and f is 1 or more.

6. The mixture for electrochemical devices according to claim 2 or 3, wherein each Rf is independently a group represented by the following formula (Rf-II) or the following formula (Rf-I-II): Formula (Rf-II): -(OC 3 F 6 )d-(OC 2 F 4 )e- (In the formula, d is an integer from 1 to 200, and e is 0 or 1.) Formula (Rf-I-II): -(OC 4 F 8 )c-(OC 3 F 6 )d-(OC 2 F 4 )e-(OCF 2 )f- (In the formula, c and d each independently represent an integer of 0 to 30, e and f each independently represent an integer from 1 to 200; the sum of c, d, e, and f is 2 or more; The order of the repeating units marked with c, d, e, or f is arbitrary.

7. The R 1 ~R 3 The mixture for electrochemical devices according to claim 2 or 3, wherein each of the groups independently represents a methyl group, an ethyl group, a trifluoromethyl group or a pentafluoroethyl group.

8. 4. The mixture for electrochemical devices according to claim 1, wherein the fibrillar resin is polytetrafluoroethylene.

9. The mixture for electrochemical devices according to any one of claims 1 to 3, wherein the electrochemical device material is an electrode active material.

10. 4. The mixture for electrochemical devices according to claim 1, wherein the fluoropolyether is liquid at any temperature between 25°C and 80°C.

11. The mixture for electrochemical devices according to any one of claims 1 to 3, wherein the content of the polyalkylene oxide represented by the following formula (6) is less than 20 mass %: (6)R 1B -(OCHR 1A (CH 2 )jCHR 2A )n-OR 2B (In the formula, R 1A and R 2A are each independently a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, j is 0 or an integer from 1 to 2; R 1B and R 2B are each independently a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, n is an integer from 5 to 1000.

12. The mixture for electrochemical devices according to any one of claims 1 to 3, further comprising a conductive assistant.

13. A mixture sheet for electrochemical devices comprising the mixture for electrochemical devices according to any one of claims 1 to 3.

14. An electrochemical device using the mixture sheet for electrochemical devices according to claim 13.

15. A step (1) of mixing a fluoropolyether, a fibrillar resin, and an electrochemical device material; and (2) rolling the mixture for use in electrochemical devices obtained in the step (1) into a sheet.

16. The method according to claim 15, wherein the fibrillary resin is polytetrafluoroethylene.

Citation Information

Patent Citations

  • High specific capacity negative electrode molding material and manufacturing method thereof and application thereof

    CN109546104A

  • Hydrogen storage alloy electrode and nickel-hydrogen battery

    JP2011040205A

  • Method for manufacturing electrode for power storage device, and power storage device

    JP2012252824A

  • Solid electrolyte slurry, method for manufacturing solid electrolyte sheet, solid electrolyte slurry inclusion body, electrode slurry, method for manufacturing electrode sheet, electrode slurry inclusion body, and method for manufacturing all-solid type lithium ion battery

    JP2016062709A

  • COMPOSITION FOR SUPPRESSING COMBUSTION IN LITHIUM-ION BATTERY

    JP2017528866A